2019
DOI: 10.1002/adma.201905879
|View full text |Cite
|
Sign up to set email alerts
|

Covalent‐Organic‐Framework‐Based Li–CO2 Batteries

Abstract: Covalent organic frameworks (COFs) are an emerging class of porous crystalline materials constructed from designer molecular building blocks that are linked and extended periodically via covalent bonds. Their high stability, open channels, and ease of functionalization suggest that they can function as a useful cathode material in reversible lithium batteries. Here, a COF constructed from hydrazone/hydrazide‐containing molecular units, which shows good CO2 sequestration properties, is reported. The COF is hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
100
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(104 citation statements)
references
References 44 publications
0
100
0
Order By: Relevance
“…For example, Loh and co-workers designed hydrazone-linked COF (Tf-DHzOPr COF) and then hybridized it with Ru@CNT (COF-Ru@CNT) as a cathode in Li-CO 2 batteries. [131] In this electrode design, the channel of COF acted as CO 2 collector and diffusion channels for both ion and gas (once interfaced to Ru@CNT). At the same time, Ru was a catalyst that was responsible for both CO 2 reduction and Li 2 CO 3 /C decomposition.…”
Section: Metal-air Batteriesmentioning
confidence: 99%
“…For example, Loh and co-workers designed hydrazone-linked COF (Tf-DHzOPr COF) and then hybridized it with Ru@CNT (COF-Ru@CNT) as a cathode in Li-CO 2 batteries. [131] In this electrode design, the channel of COF acted as CO 2 collector and diffusion channels for both ion and gas (once interfaced to Ru@CNT). At the same time, Ru was a catalyst that was responsible for both CO 2 reduction and Li 2 CO 3 /C decomposition.…”
Section: Metal-air Batteriesmentioning
confidence: 99%
“…In this regard, COFs are among the most difficult to crystallise, owing to the lesser reversibility of their covalent linkages compared to coordination bonds and hydrogen bonds in MOFs and HOFs. The ease of encoding functionalities in COFs and their structural robustness render them potentially useful in wide-ranging applications [13][14][15][16][17][18][19] . However, an in-depth understanding of the structure-property correlation in COFs is lacking, owing to the fact that most synthesised COFs are polycrystalline, which hampers structural determination.…”
mentioning
confidence: 99%
“…Li et al first reported a COF catalyst designed from hydrazide/hydrazone‐containing units for Li–CO 2 batteries ( Figure a). [ 121 ] The COF was incorporated into Ru (nanoparticles)‐decorated CNTs. The 1D channels in the catalyst could provide free paths for the diffusion of Li + ions and CO 2 , thus improving the kinetics of CO 2 reactions.…”
Section: Cathode Materials and Electrocatalysts For Li–co2 Batteriesmentioning
confidence: 99%
“…With this COF catalyst, the Li–CO 2 cell showed superior rate capability (even sustaining a high current density of 4.0 A g −1 ). [ 121 ] Huang et al developed a graphene@COF material as a cathode catalyst for Li–CO 2 batteries. [ 122 ] A uniform and thin imine COF was loaded onto graphene to assist CO 2 reactions.…”
Section: Cathode Materials and Electrocatalysts For Li–co2 Batteriesmentioning
confidence: 99%
See 1 more Smart Citation